Food quality competition among companies and government food safety supervision under asymmetric product substitution - Ningzhou Shen; Yinghua Song; Dan Liu; Dalia Štreimikienė (Amfiteatru Economic Journal, 2021)
The frequent exposures of food safety events in recent years have aroused extensive social concerns. Food quality and safety are hot topics in the food engineering field. In a market with mutual competitions, the products of different enterprises are substitutive, and enterprises have to achieve reasonable yield and to ensure product quality to maximize their profits. However, the limited production resources of enterprises affect their strategies in yield and quality. To explore enterprises' decisions in yield and food quality under no resource constraint as well as with yield and quality under resource constraints, a Cournot model with differential product substitution was constructed by using game theory, and the effects of government monitoring on food quality decision were further investigated. Results show that enterprises with strong product substitutability increase the yield and quality of their products. They can gain higher profits under no resource constraint and under resource constraint, but their profits are lower under quality constraint compared to the profits of enterprises with low product substitutability. When the equilibrium quality of enterprises is lower than the lowest quality standard requirements of the government, a high penalty ( Ø ) or a relatively low government supervision difficulty ( c ) urges enterprises to improve product quality. Under this circumstance, two enterprises produce according to the lowest quality standards. On the contrary, enterprises take certain risks to produce lowquality products to increase profits. The conclusions provide a theoretical basis to formulate food safety regulation policies from the perspective of product substitutability.
Keywords: I20; I23; O15; P46; 330; food safety; Cournot competition; asymmetric product substitution; game theory